2001
DOI: 10.1038/sj.onc.1204328
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor-mediated chromatin remodeling in vivo

Abstract: The compaction of DNA into chromatin provides an additional level of gene regulation in eukaryotes that may not be available to prokaryotes. When packaged as chromatin, most promoters are transcriptionally repressed, and transcription factors have reduced access to their binding sites. The glucocorticoid receptor (GR) is a ligand-activated transcription factor that regulates the activity of genes involved in many physiological processes. To regulate eukaryotic genes, the GR binds to target sites within promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 60 publications
1
63
0
Order By: Relevance
“…UL3 cells contain a stably integrated MMTV promoter regulating a luciferase reporter. This promoter has a normal chromatin structure including distinct nucleosomes and enhanced transcription factor binding associated with chromatin remodeling (31,32). Alternatively, an MMTV promoter regulating a CAT reporter that is transiently transfected into cells has a poorly defined chromatin structure lacking clear nucleosomes or evidence of chromatin remodeling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UL3 cells contain a stably integrated MMTV promoter regulating a luciferase reporter. This promoter has a normal chromatin structure including distinct nucleosomes and enhanced transcription factor binding associated with chromatin remodeling (31,32). Alternatively, an MMTV promoter regulating a CAT reporter that is transiently transfected into cells has a poorly defined chromatin structure lacking clear nucleosomes or evidence of chromatin remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of chromatin structure on H3 phosphorylation and osmotic response was investigated by comparing the transiently transfected MMTV promoter with a poorly organized chromatin architecture with the normal nucleosome structure of the integrated promoter (31)(32)(33). We found that osmotic stress represses hormone-dependent activation of the integrated MMTV.…”
mentioning
confidence: 99%
“…Histone H1 has clear effects on higher-order chromatin structure and phosphorylation of histone H1 is a critical component of GR-mediated MMTV activation (Bhattacharjee et al 2001, Georgel et al 2003. During GR-mediated chromatin remodeling, histone H1 is lost from the MMTV promoter (Bresnick et al 1992; reviewed in Deroo & Archer 2001, Hebbar & Archer 2003, Kinyamu & Archer 2004. Upon prolonged glucocorticoid exposure, the following prolonged exposure to hormone is accompanied by dephosphorylation of the global and promoter-associated histone H1 that is mimicked by kinase inhibitors (Lee & Archer 1998, Bhattacharjee et al 2001.…”
Section: Ubiquitin-proteasome and Nr-dependent Chromatin Remodeling: mentioning
confidence: 99%
“…Transcriptional regulation by the GR is concomitant with chromatin remodeling exemplified by restriction enzyme hypersensitivity on the MMTV promoter (reviewed in Deroo & Archer 2001, Hsiao et al 2002, Hebbar & Archer 2003. Proteasome inhibitors increase GR transactivation of the MMTV promoter in the absence of increased chromatin remodeling as measured by restriction enzyme hypersensitivity (Deroo et al 2002).…”
Section: Ubiquitin-proteasome and Nr-dependent Chromatin Remodeling: mentioning
confidence: 99%
“…Direct GR AF1:TBP interaction raises the possibility that the GR AF1 domain somehow directly influences the primary transcription machinery. In vitro transcription studies indicated that the holo-GR acts to stabilize the preinitiation complex (31,32). One possibility is that a structured conformation of AF1, induced or stabilized by its interaction with TBP, is involved in the platform for TBP-associated factors.…”
mentioning
confidence: 99%